Analysis of Broadcasting Violations Ethics at the Celeb Room Program at NET TV - Meliala, Robbikal Muntaha; Mayasari, Silvina; Fatimah, Nurul (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
Violations of broadcasting ethics are actions that violate ethical principles, violations of regulations in the guidelines applicable in the broadcasting industry. Broadcast programs are dvided into two categories, namely entertainment programs aimed at entertaining the audience and information programs aimed at increasing the audience’sknowledge. In the program “Celebrity Space” on Net Tv. Including ridicule of celebrities or public figures, gossipand personal life selebaits with taxane schedule Monday – Friday at 15.00 WIB, Duration 60 minutes, and classification R13+ (For Teenagers). Qualitative Document Study using data aggregation in the form of data analysis text, literary and image studies. Conclusion: television programs on the “Celeb Space”on Net Tv must uphold high broadcasting ethics to maintain the rights to privacy, safety and positive development of their viewers,especially children and teenager. KPI provide important guidelines to ensure that broadcast programs comply with predetermined principles.